Respuesta :
(5^2+13−4)−(172+7−19)+(5−7)⋅(3+1)=5^2+13−4−172−7+19+(15^2+5−21−7)
=562+13−4−289−7+19+152+5−21−7
=20^2−10−281
Hope it helps!
=562+13−4−289−7+19+152+5−21−7
=20^2−10−281
Hope it helps!
The polynomial expression (5x² + 13x – 4) – (17x² + 7x – 19) + (5x – 7)(3x + 1) is simplified as 3x² – 10x – 8.
What is polynomial?
A polynomial expression is an algebraic expression with variables and coefficients. Unknown variables are what they're termed. We can use addition, subtraction, and other mathematical operations. However, a variable is not divisible.
The polynomial expression is given below.
⇒ (5x² + 13x – 4) – (17x² + 7x – 19) + (5x – 7)(3x + 1)
Simplify the polynomial expression, then we have
⇒ (5x² + 13x – 4) – (17x² + 7x – 19) + 15x² – 16x – 7
⇒ 5x² + 13x – 4 – 17x² – 7x + 19 + 15x² – 16x – 7
Add and subtract like terms that mean x² term with x², x term with x, and constant term with constant.
⇒ 3x² – 10x – 8
The polynomial expression (5x² + 13x – 4) – (17x² + 7x – 19) + (5x – 7)(3x + 1) is simplified as 3x² – 10x – 8.
More about the polynomial link is given below.
https://brainly.com/question/17822016
#SPJ5